Diagnostic accuracy of ex vivo fluorescence confocal microscopy in Mohs surgery of basal cell carcinomas: a prospective study on 753 margins. (1st June 2019) - Longo, C.; Pampena, R.; Bombonato, C.; Gardini, S.; Piana, S.; Mirra, M.; Raucci, M.; Kyrgidis, A.; Pellacani, G.; Ragazzi, M.
Summary: Background: Frozen histological sections are used for intraoperative margin assessment during Mohs surgery. Fluorescence confocal microscopy (FCM) is a new tool that offers a promising and faster alternative to frozen histology. Objectives: To evaluate prospectively in a clinical setting the accuracy of FCM vs. frozen sections in margin assessment of basal cell carcinoma (BCC). Methods: Patients with BCC scheduled for Mohs surgery were prospectively enrolled. Freshly excised surgical specimens were examined by FCM and then frozen sections were evaluated. Permanent sections were obtained, in order to validate the sample technique. A blind re‐evaluation was also performed for discordant cases. Sensitivity and specificity levels, as well as positive and negative predictive values (PPV and NPV, respectively), were calculated and receiver–operating characteristic curves generated. Results: We enrolled 127 BCCs in as many patients (40·2% females). Seven hundred and fifty‐three sections were examined. All BCCs were located in the head and neck area. In evaluating the performance of FCM vs. frozen sections, sensitivity was 79·8%, specificity was 95·8%, PPV was 80·5% and NPV was 95·7% [area under the curve 0·88, 95% confidence interval 0·84–0·92 ( P < 0·001)]. Forty‐nine discordant cases were re‐evaluated; 24 were false positive and 25 false negative. The performance of FCM and frozen sections was also evaluated according to the final histopathological assessment. Conclusions: We found high levels of accuracy for FCM vs. frozen section evaluation in intraoperative BCC margin assessment during Mohs surgery. Some technical issues prevent the wide use of this technique, but new devices promise to overcome these limitations. Abstract: What's already known about this topic? Ex vivo fluorescent confocal microscopy (FCM) is a new imaging tool that offers an attractive alternative to conventional frozen histology for the detection of margins in freshly excised tissue. What does this study add? Our study of 753 specimens found that FCM is a valid imaging tool to assess basal cell carcinoma margins in Mohs surgery, with high diagnostic accuracy when compared with frozen sections. Furthermore, FCM is a safe procedure that result in few false‐negative cases when compared with permanent formalin‐embedded sections. Linked Comment:  Notingher. Br J Dermatol 2019; 180 :1295–1296 . Respond to this article